Optimization of Pre-Treatment Process in Spent Bleaching Earth (SBE) on The Characteristics of Pre-Treated SBE as Supplementary Cementitious Material - Pramono, Christian Yoga; Sutrisno, Wahyuniarsih; Triwulan, Triwulan; Aji, Pujo (Journal of Civil Engineering, 2024)
The palm oil processing industry in Indonesia has experienced significant growth, bringing both positive economic impacts and negative consequences, specifically the generation of spent bleaching earth (SBE), a waste product of bleaching earth. Despite its potential as a substitute material for cement due to its pozzolanic properties, challenges arise from SBE's oil content. Hence, this study introduces pre-treatment methods involving extraction and calcination to optimize the use of SBE, referred to as Pre-treated Spent Bleaching Earth (PSBE). This research aims to analyze the optimized PSBE material through the optimization of the pre-treatment process in the usage of mortar. The optimized PSBE is compared to another supplementary cementitious material, which is fly ash to see the performance of optimized PSBE as supplementary cementitious material. The performance of the mortar was evaluated through tests including slump test, compressive strength test, and mortar hydration temperature analysis. The pre-treatment process of SBE was optimized by combining extraction and calcination methods, which yielded the most effective results from oil content test. One of the performance analysis results showed that the compressive strength test revealed a 28-day compressive strength value of 50,22 MPa for the optimized PSBE mortar, while the fly ash mortar had a compressive strength of 37,36 MPa. In conclusion, the optimized PSBE shows promising potential as a supplementary cementitious material.